Who benefits from the earned income tax credit? Incidence among recipients, coworkers and firms - Andrew Leigh (Institute for the Study of Labor (IZA), 2010)
How are hourly wages affected by the Earned Income Tax Credit? Using variation in state EITC supplements, I find that a 10 percent increase in the generosity of the EITC is associated with a 5 percent fall in the wages of high school dropouts and a 2 percent fall in the wages of those with only a high school diploma, while having no effect on the wages of college graduates. Given the large increase in labor supply induced by the EITC, this is consistent with most reasonable estimates of the elasticity of labor demand. Although workers with children receive a much larger EITC than childless workers, and the effect of the credit on labor force participation is larger for those with children, the hourly wages of both groups are similarly affected by an EITC increase. As a check on this strategy, I also use federal variation in the EITC across gender-age-education groups, and find that those demographic groups that received the largest EITC increases also experienced a drop in their hourly wages, relative to other groups.
Keywords: H22; H23; J22; J30; 330; Taxation incidence; labor supply; simulated instrument; Negative Einkommensteuer; Steuerinzidenz; Lohn; Steuerwirkung; Arbeitsangebot; Australien